Bronchoalveolar Lavage Fluid Reflects a TH1-CD21low B-Cell Interaction in CVID-Related Interstitial Lung Disease - Friedmann, David; Unger, Susanne; Keller, Baerbel; Rakhmanov, Mirzokhid; Goldacker, Sigune; Zissel, Gernot; Frye, Björn C.; Schupp, Jonas C.; Prasse, Antje; Warnatz, Klaus (Frontiers in Immunology, 2021)
Background: About 20% of patients with common variable immunodeficiency (CVID) suffer from interstitial lung disease (ILD) as part of a systemic immune dysregulation. Current understanding suggests a role of B cells in the pathogenesis based on histology and increased levels of BAFF and IgM associated with active disease corroborated by several reports which demonstrate the successful use of rituximab in CVID-ILD. It is debated whether histological confirmation by biopsy or even video-assisted thoracoscopy is required and currently not investigated whether less invasive methods like a bronchoalveolar lavage (BAL) might provide an informative diagnostic tool. Objective: To gain insight into potential immune mechanisms underlying granulomatous and lymphocytic interstitial lung disease (GLILD) and to define biomarkers for progressive ILD by characterizing the phenotype of B- and T-cell populations and cytokine profiles in BAL fluid (BALF) of CVID-ILD compared to sarcoidosis patients and healthy donors (HD). Methods: 64 CVID, 6 sarcoidosis and 25 HD BALF samples were analyzed by flow cytometric profiling of B- and T-cells and for cytokines by ELISA and Multiplexing LASER Bead technology. Results: Both sarcoidosis and CVID-ILD are characterized by a predominantly T-cell mediated lymphocytosis in the BALF. There is an increase in T follicular helper (TFH)-like memory and decrease of regulatory T cells in CVID-ILD BALF. This TFH-like cell subset is clearly skewed towards TH1 cells in CVID-ILD. In contrast to sarcoidosis, CVID-ILD BALF contains a higher percentage of B cells comprising mostly CD21low B cells, but less class-switched memory B cells. BALF analysis showed increased levels of APRIL, CXCL10 and IL-17. Conclusion: Unlike in sarcoidosis, B cells are expanded in BALF of CVID-ILD patients. This is associated with an expansion of TFH- and TPH-like cells and an increase in APRIL potentially supporting B-cell survival and differentiation and proinflammatory cytokines reflecting not only the previously described TH1 profile seen in CVID patients with secondary immune dysregulation. Thus, the analysis of BALF might be of diagnostic value not only in the diagnosis of CVID-ILD, but also in the evaluation of the activity of the disease and in determining potential treatment targets confirming the prominent role of B-cell targeted strategies.